Corporate Social Responsibility dan Struktur Kepemilikan Serta Perannya terhadap Nilai Perusahaan - Ma'rufa, Nurzanah; Nugraha, Nugraha; Sari, Maya (Jurnal Bisnis dan Manajemen, 2021)
Firm value is the perception of investors on the value of the company's performance and the company's prospects in the future. This study aims to determine the effect of corporate social responsibility and ownership structure on firm value. The research method used is the verification method. The objects in this study are non-state-owned basic and chemical industrial companies listed on the Indonesia Stock Exchange for the period 2010-2018 with a total of 46 companies and 414 observational data. The data analysis technique used in this research is piecewise linear regression. The results of the study state that corporate social responsibility has no significant effect on firm value, ownership structure has a nonlinear relationship with firm value, and the research model on the influence of corporate social responsibility and ownership structure on firm value which is controlled by firm size, profitability, and leverage can be used to explain or predict firm value. Corporate social responsibility and ownership structure have an indirect effect on firm value.